Dispersion-free steering beam based alignment at SwissFEL. Issue 1 (1st January 2023) - Ferrari, Eugenio; Calvi, Marco; Ganter, Romain; Kittel, Christoph; Prat, Eduard; Reiche, Sven; Schietinger, Thomas
Abstract: Micron-level alignment of the undulator line is required for successful operation of linear accelerator based high gain free electron lasers to produce powerful radiation at X-rays' wavelengths. Such precision in the straightness of the trajectory allows for an optimal transverse superposition between the electrons and the photon beam. This is extremely challenging and can only be achieved via beam-based techniques. In this paper we will report on the dispersion-free steering approach implemented at SwissFEL, that helped achieving improved performance for both the hard and soft X-ray beamlines.